MAGNET WISATA RELIGI SEBAGAI PERKEMBANGAN EKONOMI MASYARAKAT DI KURAI TAJI KABUPATEN PADANG PARIAMAN - Yulie Suryani; Vina Kumala (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to describe the development of the potential for religious tourism to the communities economy in the kurai of the Padang Pariaman regency, including the process of forming tourism objects, developments tourism objects, and the impact of their development. This research is a qualitative type with a case study strategy. Data collection techniques by observation, interviews, and documentation. Test the validity of the data by triangulating data sources and data collection techniques. The data analysis used interactive techniques. This research shows that religious tourism is in visiting for pilgrimage. For this reason, development is carried out, including the addition of tourist objects such as facilities and infrastructure to make it more comfortable. From this development has a positive impact on the economy of the local community. It can be seen from the growth of various business fields, such as clothing stores, food stalls, street vendors, and entertainment.